Los paradigmas de redacción normativa como medio para alcanzar la seguridad: ¿una apuesta segura? - Fernando Centenera Sánchez-Seco (Ius Humani. Jornal do direito, 2012)
Different works concerned with the drafting of legislation consider that its language should be simple, clear and precise if it is to offer legal certainty. However legal certainty is understood, at first sight this position seems to be supported by numerous arguments, as when legal certainty is analyzed as a quality of law (in relation to accurate guidance, legal firmness and legal efficacy), as formal justice (with all that implies for liberty and equality) and as material justice (in relation, for example, to the protection of fundamental rights). However, on closer examination there also appear to be reasons for thinking that the stated paradigms for drafting do not always make for legal certainty and that in certain circumstances complex, vague or imprecise language may have its uses. That being so, the simplicity-clarity-precision guideline needs reformulating. To pursue this objective, a number of suggestive tools that may be applied to those circumstances are available in legislation theory. This paper advocates the implementation of a system of rationality which is capable of covering the diagnosed circumstances, a system organized into different levels of rationality where there would be room for both questions of language and of legal certainty.